Central bank communications before, during and after the crisis: From open-market operations to open-mouth policy - Ianthi Vayid (Bank of Canada, 2013)
The days when secrecy and opacity were the bywords of central banking are gone. The advent of inflation targeting in the early 1990s acted as the catalyst for enhanced transparency and communications in the conduct of monetary policy. In the wake of the 2007 - 09 global financial crisis, this trend accelerated, resulting in further striking advances in monetary policy and financial stability communications, including markedly the emergence of extraordinary forward guidance as a distinct policy tool under unconventional monetary policies. Drawing on the record to-date at major central banks, as well as on a growing body of related academic literature, this paper reviews the history and effectiveness of central bank communications before and especially since the crisis. It also highlights some of the challenges facing central banks, particularly those that have engaged heavily in unconventional monetary policies to support their economies since the crisis. Steering deftly a course back to normality will depend crucially on their ability to communicate effectively a credible strategy for an orderly exit from such policies. In this context, clear, deliberate, coordinated messages that are anchored in their mandate are of the essence.
Keywords: E52; E58; 330; Central bank research; Credibility; Financial stability; Inflation targets; Monetary policy framework; Monetary policy implementation